Fatigue life of hybrid metal composite materials: A review - Rashid, Yaseen; Fadhil, Basim M.; Ramadan, Dlair O. (Al-Nahrain Journal for Engineering Sciences, 2026)
Hybrid metal composite materials, combining diverse metal components, have emerged as promising alternatives in engineering applications, offering a unique synergy of mechanical properties. This review comprehensively examines the fatigue life of hybrid metal composites, delving into the intricate interplay of materials, manufacturing processes, and environmental factors. Drawing from a rich array of literature, the review explores the evolution of hybridization strategies, emphasizing their impact on fatigue resistance. Key factors influencing fatigue behavior, including material selection, manufacturing techniques, and environmental conditions, are systematically analyzed. The article highlights the significance of strategic hybridization in enhancing fatigue characteristics, reducing costs, and optimizing the overall performance of metal composites. The insights presented contribute to advancing the understanding of fatigue mechanisms in hybrid metal composite materials, offering valuable guidance for future research and engineering applications. Hybrid metal composite materials, characterized by the combination of diverse metal components, have garnered significant attention in engineering applications due to their potential to provide a unique synergy of mechanical properties. This comprehensive review delves into the intricate aspects of the fatigue life of hybrid metal composites, offering a thorough analysis of the interplay between materials, manufacturing processes, and environmental factors.